The Sufficiency-Based Circular Economy—An Analysis of 150 Companies - Bocken, Nancy M. P.; Niessen, Laura; Short, Samuel W. (Frontiers in Sustainability, 2022)
The circular economy has become a popular paradigm in the business and policy spheres. It can support sustainable development by aiming to safeguard the resources to mitigate negative impacts on the climate and the environment and to sustain our current and future generations. Yet, despite progress with circular economy initiatives, there is a risk of focusing on incremental innovations with little real impact, and possibly even creating serious negative rebound effects. This study suggests that the concepts of ‘sufficiency’ and ‘enough’ are inadequately represented in the current circular economy discourse and innovations, and this blind spot may be undermining real progress. In this paper, the Sufficiency-based Circular Economy paradigm is introduced. We investigate the following questions: What is the role of business in the sufficiency-based circular economy? What are the institutional limitations to the role of business as a driver for the transition and how might these be overcome? We conduct a ‘practice research’ by analysing company cases of sufficiency practices in a business context. We analyse 150 business cases to identify how their organizational strategies support sufficiency and what type of innovations they exemplify within this transition. We investigate the purpose, ownership, governance, finance, networks, scale-up and impact of these businesses to understand how these drive the value propositions and customer engagement and their impact on the wider transition. The proposed benefits and potential negative rebound effects are discussed. This is followed by a discussion on a broader business and policy perspective of the Sufficiency-based Circular Economy. Finally, future pathways for research and practice are described.